Coping with illness - Miles, Liz. (Chicago : Heinemann Library, 2011)
Discusses illness and how it can affect a family, describing common, long-term, and terminal illnesses, and providing tips and advice for children to care for themselves and others, and cope with illness.
Includes bibliographical references (p. 46-47) and index.
Library Media Connection
Library Media Connection, January 2012
Young Adult.
Young Adult
Keywords: Children -- Diseases -- Juvenile literature; Diseases -- Juvenile literature; Diseases; Diseases